Serotonergic markers in Parkinson's disease and levodopa‐induced dyskinesias. Issue 6 (4th February 2015) - Cheshire, Perdita; Ayton, Scott; Bertram, Kelly L.; Ling, Helen; Li, Abi; McLean, Catriona; Halliday, Glenda M.; O'Sullivan, Sean S.; Revesz, Tamas; Finkelstein, David I.; Storey, Elsdon; Williams, David R.
Abstract Preclinical animal models implicate serotonin neurons in the pathophysiology of levodopa (l‐dopa)–induced dyskinesias in Parkinson's disease (PD), but effective treatment remains elusive. We examined the relationship between serotonin and l‐dopa–induced dyskinesias in a pathologically confirmed cohort of PD patients. We obtained brain tissue from 44 PD cases and 17 age‐matched controls and assessed monoamine levels and the serotonin and dopamine transporters in the striatum, and the extent of dopaminergic and serotonergic cell preservation in the substantia nigra (SN) and the dorsal raphe nuclei (DRN), respectively. As expected, PD patients demonstrated a severe loss of all dopaminergic markers, including dopamine (P < 0.0001) and the dopamine transporter (P < 0.0001) in the striatum, and dopaminergic neurons (P < 0.001) in the SN, compared with controls. Marked serotonin loss was observed in the caudate (but not putamen) in PD patients compared with controls (P < 0.001), but no difference was found in the levels of the serotonin transporter in the striatum or density of serotonergic neurons in the DRN between these groups, suggesting a functional but not structural change in the serotonergic system in PD. No difference was seen in levels of serotonergic and dopaminergic markers in the striatum between PD patients with and without dyskinesias, or between cases separated according to the clinical severity of their dyskinesias. The absence of a correlation between striatal serotonin markers and the incidence and severity of l‐dopa–induced dyskinesias suggests that an intact and functioning serotonergic system is not a risk factor for developing dyskinesias in PD. © 2015 International Parkinson and Movement Disorder Society